Linguistic Consistency of Goal Models - Pittke, Fabian; Nagel, Benjamin; Engels, Gregor; Mendling, Jan (Proceedings of the 19th International EMMSAD Conference)

Breathing Life into Situational Software Engineering Methods - Fazal-Baqaie, Masud; Gerth, Christian; Engels, Gregor (In Proceedings of the 15th International Conference of Product Focused Software Development and Process Improvement (PROFES 2014))
Software engineering methods are used to prescribe and coordinate the tasks necessary to plan, build, deliver, and maintain software. There is a broad consensus that there is no one-size-fits-all method and that, e.g., agile and plan-driven approaches have to be mixed sometimes, based on the context of a project. Creating these so-called situational methods and assuring that they cover all necessary details consistently is a challenge. There is also the challenge for the project teams to follow methods as prescribed by the method engineer. Our approach supports the creation of consistent situational methods from a repository of pre-existing building blocks. Moreover, we present means to enact these methods with standard BPEL/BPEL4People workflow engines, automating the coordination of tasks and providing guidance for them.

Agile Entwicklung mit On- und Offshore-Partnern – Methodenverbesserung in der Praxis - Fazal-Baqaie, Masud; Sauer, Stefan; Heuft, Torsten (Proceedings of Projektmanagement und Vorgehensmodelle 2014)
Agile Softwareentwicklungsmethoden erfreuen sich einer steigenden Verbreitung, versprechen sie doch risiko-getrie-ben und leichtgewichtig auch bei sich verändernden Anforderungen gute Ergebnisse zu erzielen. Viele Unternehmen stehen jedoch vor der Herausforderung, agile Prinzipien mit den Gegebenheiten im Unterneh-men zu vereinbaren, z.B. mit den internen Prozessen und organisatori-schen Gegebenheiten. Ein besonders herausforderndes Beispiel ist die Softwareentwicklung in Kooperation mit Offshore-Partnern. Die Auto-ren berichten aus einem laufenden Methodenverbesserungsprojekt für ein Unternehmen der Finanzbranche, das für die Softwareentwicklung mit On- und Offshore-Partnern kooperiert. Anders als bisher soll der indischen Offshore-Partner in naher Zukunft große Softwaressysteme federführend implementieren. Dabei sollen projektindividuell auch Onshore-Partner eingebunden werden. Der Beitrag stellt den systema-tischen Ansatz für die inkrementelle Methodenverbesserung vor, mit dem Varianten einer möglichst agilen Methode definiert werden sollen, die sowohl im Projektumfeld als auch im operativen Tagesgeschäft ef-fektiv und effizient eingesetzt werden können. Die Autoren fassen au-ßerdem die im Rahmen von Interviews erhobenen, bisherigen Erfah-rungen in der Zusammenarbeit mit dem Offshore-Partner zusammen, die für die Methode berücksichtigt werden müssen.

Configuration of Specification Language and Matching for Services in On-The-Fly Computing - Arifulina, Svetlana; Christin Platenius, Marie; Gerth, Christian; Becker, Steffen; Engels, Gregor; Schäfer, Wilhelm

Model-Based User Interface Development for Adaptive Self-Service Systems - Yigitbas, Enes; Fischer, Holger Gerhard; Sauer, Stefan (Design, User Experience, and Usability. Theories, Methods, and Tools for Designing the User Experience - Third International Conference, DUXU 2014, Held as Part of HCI International 2014, Heraklion, Crete, Greece, June 22-27, 2014, Proceedings, Part I)

Model-Based Development of Adaptive UIs for Multi-channel Self-service Systems - Yigitbas, Enes; Fischer, Holger Gerhard; Kern, Thomas; Paelke, Volker (Human-Centered Software Engineering - 5th IFIP WG 13.2 International Conference, HCSE 2014, Paderborn, Germany, September 16-18, 2014. Proceedings)

Flexible & Adaptive UIs for Self-Service Systems - Yigitbas, Enes; Sauer, Stefan (Mensch & Computer 2014 - Workshopband, 14. Fachübergreifende Konferenz für Interaktive und Kooperative Medien - Interaktiv unterwegs - Freiräume gestalten, 31. August - 3. September 2014, München, Germany)

Qualität im Usability Engineering - Stand der Arbeiten am Qualitätsstandard Usability Engineering der German UPA - Fischer, Holger Gerhard; Riedemann, Catharina; Daske, Lisa; Geis, Thomas; Kluge, Oliver; Molich, Rolf; Polkehn, Knut (Jahresband Usability Professionals)

IT-Unterstützung im praktischen Ausbildungsbetrieb der Feuerwehr - Senft, Björn; Fischer, Holger Gerhard; Sudbrock, Christian (Mensch & Computer 2014 - Workshopband)

Vehicular Networking - Sommer, Christoph; Dressler, Falko
The intensive use of networked embedded systems is one of the key success factors in the automotive industry also triggering a massive shortening of innovation cycles. Hundreds of so called Electronic Control Units (ECUs), connected by kilometers of electrical wiring, operate in today's modern car enabling a huge variety of new functionalities ranging from safety to comfort applications. All this functionality can only be realized if the ECUs are able to communicate and to cooperate using a real-time enabled communication network in the car. Today we are at the verge of another leap forward: This in-car network is being ex- tended to not only connect local ECUs but to connect the whole car to other cars and its environment using Inter-Vehicle Communications (IVCs). Relying on existing wireless Internet access using cellular networks of the third (3G) or fourth generation (4G), or novel networking technologies that are being designed specifically for the use in the vehicular context such as IEEE WAVE, ETSI ITS-G5, and the IEEE 802.11p protocol, it becomes possible to use spontaneous connections between vehicles to exchange information, promising to enable novel and sometimes futuristic applications. Using such IVC, safety relevant information can be exchanged that could not have been obtained using local sensors, enabling a driver to virtually see traffic through large trucks or buildings. This new idea of networked vehicles creates opportunities to not only increase road traffic safety but also to improve our driving experience. Traffic jams can be prevented altogether (or at least we would be informed of jams well in advance) - and we might even be able to enable the driver to enjoying fully automated rides in a train-like convoy of cooperating of vehicles on the road. Vehicular networking, the fusion of vehicles' networks to exchange information, is the common basis on which all of these visions build upon. Being fascinated with all the opportunities and challenges related to vehicular networking, we have been a part of this research community for close to ten years. In this time, many new and sometimes crazy ideas have been formulated how to connect cars of the future. Many of these ideas have been found not suitable after thorough investigation - yet, several survived and paved the road for what are now close to market-ready solutions. From a research perspective, we are able to identify many open challenges, both in the in-car and inter-vehicle communication systems. To investigate these further, we co-organized two Dagstuhl seminars inviting leading experts from all over the world and bringing together practitioners from industry and scientists from research institutes and universities. In this scope, we were able to formulate directions guiding the ongoing research activities at least in the medium term. We also established a complementary seminar series for newcomers to the field, which is being organized in the context of the international FG-IVC series of seminars and organized by the German computer science and electrical engineering societies GI and ITG. This textbook is based on a tutorial series on the same topic presented at all the major IEEE conferences including IEEE CCNC, IEEE ICC, IEEE GLOBECOM, and IEEE VTC, as well as in the scope of Falko Dressler's IEEE Distinguished Lecturer Tours in Europe, the U.S., South America, and Asia-Pacific. We also designed a new graduate level university class, which is being held at different universities in Europe. This has inspired us to collect our experiences in the form of a textbook, collecting in one place the common concepts of past and future vehicular networking topics for a broad range of readers - from students that want to enter this exciting new field to practitioners looking for a comprehensive overview. This book would not have been possible without the many people that have inspired and supported us over the last decade in our research activites on vehicular networking - first and foremost the community centering around the IEEE Vehicular Networking Conference, the premier conference in the field. In particular we'd like to name Prof. Ozan K. Tonguz (CMU) and Prof. Mario Gerla (UCLA) who collaborated with us investigating some of the mentioned crazy ideas, and finally identifying valuable and lasting solutions. The aforementioned tutorial lectues have been prepared together with Dr. Onur Altintas (Toyota ITC) and Prof. Claudio Casetti (Politechnico di Torino). We also wish to express our appreciation for the support we received from the most helpful staff at Cambridge during the preparation of this book. Finally, we would like to sincerely thank our families, friends, and colleagues for their enduring help and support. We hope you will enjoy reading this textbook as much as we enjoyed preparing its contents for you. We gladly welcome any feedback and invite you to leave us a note or peruse supplementary material we are offering on this book's companion website http://book.car2x.org/.